Investigation of the spiral secretion pattern of the serine protease autotransporter, EspC using innovative fluorescent labelling approaches - Ashawesh, Mahmoud (2016)
Enteropathogenic Escherichia coli (EPEC) is a diarrheagenic pathogen belonging to the Enterobacteriaceae and considered to be a leading cause of acute infantile diarrhoea in developing nations. During onset of infection, EPEC inject a variety of effector proteins into the host epithelial cells using the type III secretion system (T3SS). These effectors are encoded within the pathogenicity island (PAI) called the locus of enterocyte effacement (LEE). EPEC also secretes the non-LEE encoded serine protease EspC (EPEC secreted protein C) into the extracellular milieu. This autotransporter (AT) exits EPEC through a type V secretion system (T5SS) and is subsequently delivered into host cells by the T3SS. The precise steps by which EspC is secreted are still unknown. By using both traditional and advanced optical microscopes, it is shown here that EspC tagged with two different fluorescent labels locates to a structure that resembles the spiral bacterial cytoskeleton when it has its β-barrel domain attached. It was discounted that the spiral formation was an artefact of aggregation. Moreover, production of another AT (AaaA, derived from Pseudomonas aeruginosa) also generated spiral structures that resemble the ones observed with EspC. Perturbing the structure of the bacterial cytoskeleton actin homologue MreB with the S-(3,4-dichlorobenzyl) isothiourea compound (A22) disrupted the localization of EspC-mCherry. Furthermore, producing EspC-mCherry in an E. coli SecA mutant generated altered localization patterns. Collectively, these results indicate that the spiral localization of EspC is dependent upon its C-terminal β-barrel domain, the Sec translocon and the actin homologue MreB and this spiral secretion pathway seems to be conserved among ATs. Further analysis is required to reveal the molecular mechanism underlying spiral formation to unravel the mystery of AT secretion, thereby enabling the development of new therapeutic targets and treatments.